2016
DOI: 10.1152/ajpendo.00486.2015
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome biogenesis may augment resistance training-induced myofiber hypertrophy and is required for myotube growth in vitro

Abstract: Stec MJ, Kelly NA, Many GM, Windham ST, Tuggle SC, Bamman MM. Ribosome biogenesis may augment resistance training-induced myofiber hypertrophy and is required for myotube growth in vitro. Am J Physiol Endocrinol Metab 310: E652-E661, 2016. First published February 9, 2016 doi:10.1152/ajpendo.00486.2015.-Resistance exercise training (RT) is the most effective method for increasing skeletal muscle mass in older adults; however, the amount of RT-induced muscle growth is highly variable between individuals. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
195
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 132 publications
(216 citation statements)
references
References 49 publications
15
195
5
1
Order By: Relevance
“…Correlative evidence supporting satellite cell–mediated myonuclear addition during human RT-induced myofiber hypertrophy gained traction in the mid-2000s (e.g., Olsen et al 2006; Petrella et al 2006, 2008) and studies reporting modest hypertrophy with no appreciable myonuclear addition (Petrella et al 2006, 2008; Verdijk et al 2009) fueled the concept of reaching a domain ceiling that led to a “demand” for nuclear addition. This concept was reaffirmed recently as moderate myofiber hypertrophy was accomplished in older adults in the absence of myonuclear addition, whereas nuclear addition accompanied greater hypertrophy (Stec et al 2016). New research leveraging the Pax7-DTA satellite cell depletion mouse and myonuclear transcription rates lends additional support for myonuclear reserve capacity (i.e., expansion of the domains before demanding additional nuclei) (Kirby et al 2016).…”
Section: Muscle Stem (Satellite) Cell Activitymentioning
confidence: 68%
See 3 more Smart Citations
“…Correlative evidence supporting satellite cell–mediated myonuclear addition during human RT-induced myofiber hypertrophy gained traction in the mid-2000s (e.g., Olsen et al 2006; Petrella et al 2006, 2008) and studies reporting modest hypertrophy with no appreciable myonuclear addition (Petrella et al 2006, 2008; Verdijk et al 2009) fueled the concept of reaching a domain ceiling that led to a “demand” for nuclear addition. This concept was reaffirmed recently as moderate myofiber hypertrophy was accomplished in older adults in the absence of myonuclear addition, whereas nuclear addition accompanied greater hypertrophy (Stec et al 2016). New research leveraging the Pax7-DTA satellite cell depletion mouse and myonuclear transcription rates lends additional support for myonuclear reserve capacity (i.e., expansion of the domains before demanding additional nuclei) (Kirby et al 2016).…”
Section: Muscle Stem (Satellite) Cell Activitymentioning
confidence: 68%
“…This strategy has yielded valuable insight into potential cellular and molecular regulators of human RT-induced myofiber hypertrophy (Bamman et al 2007; Kim et al 2007; Petrella et al 2008; Mayhew et al 2011; Thalacker-Mercer et al 2013). We have since validated the utility of the model (Stec et al 2016) and today similar strategies used by a number of research teams continue to bear fruit (Davidsen et al 2011; Prestes et al 2015; Ahtiainen et al 2016; Ogasawara et al 2016). Of course all participants in RT trials benefit to varying degrees in other ways (Bamman et al 2007; Bickel et al 2011; Churchward-Venne et al 2015) (e.g., strength gains, functional mobility improvements, etc.)…”
Section: Leveraging Human Interindividual Response Heterogeneitymentioning
confidence: 94%
See 2 more Smart Citations
“…Recent research has reported that an acute bout of resistance exercise in rodents West et al, 2016) and humans (Stec et al, 2015) increases ribosome content or 45S pre-rRNA (which is a precursor to 28S, 18S and 5.8S rRNA (Chaillou et al, 2014 (Kirby et al, 2015) similarly reported that 14 days of synergist ablation in 5-mo-old mice, which elicited a 71% increase in plantaris mass, induced a twofold increase in ribosome content and increased the mRNA expression of numerous ribosomal proteins. In humans, Stec et al (Stec et al, 2016) reported that 4 weeks of lower body resistance training increased vastus lateralis mixed-fibre total RNA levels in "extreme responders"…”
Section: Discussionmentioning
confidence: 99%